Model order reduction for non-linear quasi-electrostatic problems - Yuqing Xie; Lin Li; Shuaibing Wang (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
In order to reduce the computational complexity and computational time for the non-linear quasi-electrostatic problems, the reduced order finite element model based on proper orthogonal decomposition (POD) and discrete empirical interpolation (DEIM) is proposed. The presented reduced order algorithm is applied to compute the electrical field distribution in the winding end of a type of ±500kV converter transformer on the polarity reverse condition. The numerical results show that the computation result of the proposed POD-DEIM reduced order method is in good agreement with that of full order finite element method.